2015
DOI: 10.1021/acsbiomaterials.5b00356
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous Snake Venom Hemostat

Abstract: Controlling perioperative bleeding is of critical importance to minimize hemorrhaging and fatality. Patients on anticoagulant therapy such as heparin have diminished clotting potential and are at risk for hemorrhaging. Here we describe a self-assembling nanofibrous peptide hydrogel (termed SLac) that on its own can act as a physical barrier to blood loss. SLac was loaded with snake-venom derived Batroxobin (50 μg/mL) yielding a drug-loaded hydrogel (SB50). SB50 was potentiated to enhance clotting even in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…18 For example, Kumar et al reported that snake venom laded self-assembling nanofibrous peptide hydrogel is a facile method for surgical hemostasis. 19 Similarly, Hsu et al showed that self-assembling peptides, especially RADA16-I, are highly effective in generating in hemostasis with a hemostasis time of <10 s. 20 In their study, an antibiotic released self-assembled film developed for rapid hemostat. 21 Recently, self-assembling peptide scaffolds have been under extensive investigations for effective hemorrhage control.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…18 For example, Kumar et al reported that snake venom laded self-assembling nanofibrous peptide hydrogel is a facile method for surgical hemostasis. 19 Similarly, Hsu et al showed that self-assembling peptides, especially RADA16-I, are highly effective in generating in hemostasis with a hemostasis time of <10 s. 20 In their study, an antibiotic released self-assembled film developed for rapid hemostat. 21 Recently, self-assembling peptide scaffolds have been under extensive investigations for effective hemorrhage control.…”
Section: Introductionmentioning
confidence: 97%
“…These materials have several problems, such as batch‐to‐batch variability and carry risk of biological contamination, because of xeno‐/allogenic characteristics . For example, Kumar et al reported that snake venom laded self‐assembling nanofibrous peptide hydrogel is a facile method for surgical hemostasis . Similarly, Hsu et al showed that self‐assembling peptides, especially RADA16‐I, are highly effective in generating in hemostasis with a hemostasis time of <10 s .…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled traumatic and surgical bleeding are leading causes of fatality (casualties) in warfare, accidents, disaster, and crime . Excessive bleeding disrupts hemodynamics, requires transfusions, prolongs operative time, and adds a huge burden on healthcare system . Hemorrhage accounts for about 35% of trauma mortality, and 40% of these deaths happens before admission to the hospital .…”
Section: Introductionmentioning
confidence: 99%
“…In cases of severe or uncontrolled blood loss, the body's natural clotting process is not able to facilitate hemostasis on its own, which calls for external hemostasis. The critical design requirements for the hemostats are to 1) provide a localized physical barrier to entrap red blood cells (RBC), 2) provide a chemical platform that accelerates clotting regardless of the presence of heparin, 3) stop bleeding in a rapid fashion (<1 min), and 4) prevent hemorrhaging during subsequent manipulation …”
Section: Introductionmentioning
confidence: 99%
“…However, this technology shows promise for use in embolic applications. Another recently developed hydrogel‐based hemostatic material includes an injectable nanofibrous peptide hydrogel that has been loaded with snake‐venom derived Batroxobin . The material promotes clotting by physically blocking blood flow and utilizing a hemostatic drug, even in the presence of heparin, resulting in improved liver incision hemostasis in a rat model in comparison to clinical controls.…”
Section: Introductionmentioning
confidence: 99%